Focused wave interactions with floating structures: a blind comparative study. Issue 1 (4th March 2021) - Ransley, Edward J.; Brown, Scott A.; Hann, Martyn; Greaves, Deborah M.; Windt, Christian; Ringwood, John; Davidson, Josh; Schmitt, Pal; Yan, Shiqiang; Wang, Junxian X.; Wang, Jinghua H.; Ma, Qingwei; et al.
Abstract : The paper presents results from the Collaborative Computational Project in Wave Structure Interaction (CCP-WSI) Blind Test Series 2. Without prior access to the physical data, participants, with numerical methods ranging from low-fidelity linear models to fully non-linear Navier–Stokes (NS) solvers, simulate the interaction between focused wave events and two separate, taut-moored, floating structures: a hemispherical-bottomed cylinder and a cylinder with a moonpool. The 'blind' numerical predictions for heave, surge, pitch and mooring load, are compared against physical measurements. Dynamic time warping is used to quantify the predictive capability of participating methods. In general, NS solvers and hybrid methods give more accurate predictions; however, heave amplitude is predicted reasonably well by all methods; and a WEC-Sim implementation, with CFD-informed viscous terms, demonstrates comparable predictive capability to even the stronger NS solvers. Large variations in the solutions are observed (even among similar methods), highlighting a need for standardisation in the numerical modelling of WSI problems.